Peran Komunikasi Organisasi dalam Membangun Tim Kerja yang Efektif: Studi Literatur - Fadilul Rahman; Julia Salsabila; Novriyanti Achyar (GLOBAL SCIENTS PUBLISHER, 2025)
This study examines the role of organizational communication in building effective work teams within modern organizational settings. The core issue addressed is that many organizations continue to experience miscommunication, limited coordination, and weak team cohesion, which hinder overall performance. The purpose of this study is to identify the key elements of organizational communication that contribute to team effectiveness, explain the mechanisms through which communication influences team outcomes, and describe the challenges and strategies for optimizing communication practices. This research employs a literature review method by analyzing relevant journal articles, books, and academic publications. The results indicate that effective communication implemented through vertical, horizontal, and diagonal channels plays a crucial role in enhancing coordination, fostering trust, and strengthening collaboration among team members. Furthermore, clear and open communication improves productivity, reduces misunderstandings, and supports shared understanding within the team. The study also highlights that communication serves not only as a tool for transmitting information but also as a strategic component that shapes team dynamics and long-term performance. Overall, the findings emphasize the need for organizations to systematically manage communication practices in order to develop and maintain effective work teams.